Formulation and evaluation of liquid soap preparation of robusta green coffee extract (Coffea canephora) with virgin coconut oil (VCO) base as an antibacterial Staphylococcus aureus - Ing Mayfa Br Situmorang; Feronika Evma Rahayu; Opi Dwi Nurhayati (Pascasarjana Universitas Negeri Medan, 2023)
Staphylococcus aureus can be found on the surface of the skin. One way to prevent Staphylococcus aureus on the skin is to clean the skin with soap. Liquid soap effectively removes dirt from the skin surface and protects the skin from bacteria. Determining the robusta green coffee bean extracts (Coffea canephora) appropriate activity was the study’s major aim in a liquid soap that complies with SNI 06-4085-1996 for use as an antibacterial agent and meets the physical quality requirements for liquid soap preparations. The extraction is performed by a soxhlet extraction method with 96% ethanol. The results of the organoleptic test show a difference in color at each concentration, with the concentration of the extract, which is higher, affecting the color and odor, the results of the homogeneity show results that are homogeneous and free of coarse grains, the results of the pH test show results that meet the requirements, namely in the interval 8-11, the results of the viscosity show results that meet the SNI requirements of 400-4000Cps, the results of the foam height test show stable results and meet the SNI requirements of 13-220 mm. the results of the inhibition zone in the liquid bath soap preparation of robusta green coffee bean extract using the disk diffusion method show that F0 = 4.51mm (resistant), F1 = 11.11mm (resistant), F2 = 13.35mm (intermediate) and F3 = 20.57mm (suspicious).Keywords: Coffea canephora; Disc diffusion; Liquid soap; Staphylococcus aureus